A Mycoplasma protein homologous to mammalian SRP54 recognizes a highly conserved domain of SRP RNA. - Samuelsson, T (1992)
A protein homologous to SRP54, a subunit of the mammalian signal recognition particle (SRP), was identified in Mycoplasma mycoides. The mycoplasma protein was expressed in E.coli and purified to near homogeneity. It was shown to bind specifically in vitro to a small mycoplasma RNA with structural features related to the RNA component of SRP. These findings provide evidence of a ribonucleoprotein complex in mycoplasma reminiscent of SRP. A part of the RNA was protected from ribonuclease digestion in the presence of the SRP54 homologue. The protected region contains structural elements that have been highly conserved in SRP RNAs during evolution.